1982
DOI: 10.1051/rnd:19820710
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 2 Br-α-ergocryptine (CB 154) on the secretion of prolactin, LH, FSH and testosterone and on testicular growth in rams subjected to different photoperiods

Abstract: Summary. The influence of 2-Br-a-ergocryptine (CB 154) on the secretion of gonadotrophins and on testicular function has been studied in rams subjected to either a normal photoperiod or an abnormal photoperiod causing hyperprolactinaemia. The CB 154 treatment significantly lowered the mean frequency of LH and testosterone pulses in hyperprolactinaemic animals as compared to solvent-treated ones. Also, only those groups subjected to an abnormal photoperiod (groups 2 and 3) exhibited a significant rise in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2

Year Published

1986
1986
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
1
8
2
Order By: Relevance
“…The mechanism of this effect is unclear: bromo¬ criptine treatment has been reported to stimulate FSH release in sheep (Ravault et al, 1982), but no such effect was seen in the present study (Fig. lb).…”
Section: Discussioncontrasting
confidence: 66%
“…The mechanism of this effect is unclear: bromo¬ criptine treatment has been reported to stimulate FSH release in sheep (Ravault et al, 1982), but no such effect was seen in the present study (Fig. lb).…”
Section: Discussioncontrasting
confidence: 66%
“…(1) Land, Carr, McNeilly & Preece (1980), Ravault, Barenton, Blanc et al (1982) and Schanbacher (1980) failed to alter gonadal activity under long days by sup¬ pressing prolactin secretion through administration of bromocriptine to ewes, and (2) the present results revealed that the gonadal activity in response to long days was not necessarily reciprocal to prolactin secre¬ tion in SCGX goats. It is likely, therefore, that melatonin mediated the response of gonadal function and prolactin secretion to long days independently.…”
Section: Discussioncontrasting
confidence: 62%
“…In some species such as the rat and the ram, the injection of bromo¬ criptine into normal animals does not induce changes in reproductive function (Skett, Eneroth & Gustafsson, 1978;Poindron, Cognie, Gayerie et al 1980;Doherty et al 1981), but delays puberty in immature female rats (Shaban & Terranova, 1986). In contrast, admin¬ istration of bromocriptine to hyperprolactinaemic animals induces changes in sexual function which dif¬ fer according to species: testosterone concentrations are decreased and LH concentrations increased in the golden hamster (Bex, Bartke, Goldman & Dalterio, 1978), LH concentrations are decreased without changes in testosterone concentrations in the ram (Ravault, Barenton, Blanc et al 1982), and LH con¬ centrations are increased in the rat (Doherty et al 1981). In fact, two systems for the regulation of pro¬ lactin secretion and its relationship with reproductive functions seem to be implicated: the first one under photoperiodic control and the second depending on stress factors including pheromonal effects ).…”
Section: Discussionmentioning
confidence: 89%